(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
It is impossible to imagine that a person can find his place in life, achieve the happiness of two worlds, contribute to the development of his country and become a worthy child of this country without education. We can compare this to the fact that a bird could not fly to the sky without two wings.Allah Almighty says in verse 6 of Surah "Tahrim": "O you who believe! Protect yourself and your family from the fire fueled by people and stones." How can a man protect himself, his wife, and his dependents from the fire? This protection is first of all by removing ignorance from people after themselves, and protecting them from various crimes and sins, ignorance and vices, which lead to the fire in the life of the world, through education and training.